Colonialism and a history of oppression in Africa: Scenes from selected African novels - Ismail, Hisham Muhamad (Research Journal in Advanced Humanities, 2023)
Examining the African suffering during the colonialism period and describing the different miseries of the African people have been the core theme of almost all African and Western writers during the colonial age and post-colonial time. Undoubtedly, all of these writings fluctuate considerably between exaggeration and degrading the human sacrifices of those countries during this period. Then, the African writers started taking the responsibility of narrating their history and describing their suffering to correct many false ideas and assumptions, many false conceptions which were established in the minds of consecutive generations. Chinua Achebe is one of the prominent authors and thinkers who has received international recognition due to his creative style of telling the African story and has impacted African literature in different ways. Through his books, he exposed many of the negative colonial impacts on the African communities and how they did their best to invade these countries politically, economically, and culturally. Achebe tried to uncover their claims, like linking Christianity and commerce together, and the only way to African progress should be through the European gates. In his novel Things Fall Apart, he tried to expose the side effects of the colonizers’ intentions to redesign the African communities up to Western standards. He assured that all colonial actions resulted in the colonizers’ good interests and were against African people. On the other hand, Ngugi Thiogn’o is interested in examining the post-colonial impacts on the African nations and how the Western colonizers succeeded in producing loyal followers adopting their beliefs and concepts. Those followers replaced the foreign occupation with another type of occupation where the people’s acceptance should be evaluated by their adaptability to the Western criteria in all life aspects. In his novel, Pedals of Blood, Thiog’o narrated the impacts of using foreign languages to diffuse the indigenous culture and lose the African identity. Throughout the novel, he examined the political elite’s corruption in African countries during the post-colonial period and how they continued colonial suppression of their nations.